Management guide to condition monitoring in manufacture - Davies, A. (Alan). (London Institution of Production Engineers, 1990)
This book is simply intended to be a guide to the subject, to enable those wishing to implement Condition Monitoring to be more aware of the nature and benefits of its practice and techniques, and so help them to get started. In fact, to date everything suggests that British industry is somewhat unaware of the potential advantages that Condition Monitoring can bring to sharpen the competitive edge - and that many producers are quite uniformed even of the method and application of Condition Monitoring itself, as an aid to reliable production and for maintaining the condition of factories at peak performance. To be totally effective in a modern manufacturing application, Condition Monitoring should be considered firstly at the design stage; as "built-in", and then as part of an on-going Condition Based Maintenance policy. It is essentially plant Predictive Maintenance by "health checks", conducted throughout the equipment life-cycle. So as such, this guide is deliberately not exhaustive in its coverage, but highlights the main ingredients, the various aspects being simply expressed and supported by additional reading and where to get help if desired.
Electronic reproduction.
Keywords: Engineering economy; Expert systems (Computer science); Machinery -- Monitoring; Electronic books